A TransIndigenous Study of Indigenous Australian and Adivasi/Tribal Literatures: Seeking Literary and Thematic Connections ... - Shivadas, Priyanka (UNSW Sydney, 2022)
This thesis juxtaposes Indigenous Australian literature and Adivasi/tribal literature—two self-governing bodies of Indigenous literature differently situated: one in an Anglophone, white settler-nation in the Pacific region and the other in a non-Anglophone, postcolonial nation-state in Asia. Studies exploring critical connections between Indigenous writing from Australia and Adivasi/tribal writing from India are rare. A considerable amount of scholarship brings together the literatures of Indigenous Australians, Māori, Native American and First Nations peoples of Canada, who share much in their responses to European settler-colonialism, but little ventures into comparative study of the literatures of the Indigenous peoples of Australia and India. This thesis is guided by Native American scholar Chadwick Allen’s trans-Indigenous methodologies, which open up possibilities for global Indigenous literary studies by building from specificities and across, through and beyond differences in diverse Indigenous ...